The 'ordinary-ization' of televised cooking expertise: A historical study of cooking instruction programmes on Swedish television. (September 2016) - Eriksson, Göran
Abstract: Taking a historical perspective (1982–2005) and using a multimodal discourse analysis, this paper explores the performance of ordinary expertise in Swedish cookery programmes. In particular it explores the changing forms of audience address in one particular format, called the novice format, which is crucial to understanding the history of Swedish cookery programmes. Typically this format involves two participants: a presenter who plays the role of a novice cook, posing questions about the ongoing preparation of dishes; and a chef who carries out the cooking, providing expert advice by responding to the questions asked. The analysis shows that over time the performance of expertise goes from taking the form of conversational coaching, to being enacted through small talk, to finally arising through the simulation of an interactional give-and-take between the expert and the viewers. When it comes to the ordinariness of ordinary expertise, this development is paradoxical. In the later series of programmes, when the chef appears more like an ordinary guy, the distance between the expert chef and the viewers is reduced. But at the same time the cooking is decoupled from routines associated with work and domestic chores, and in this sense is becoming less tied to everyday life and more escapist in character.